The relationship of crowd management strategies and safety performance among sport tourism event venue organisers in Kuala Lumpur and Selangor / Norazlina Rahmat - Rahmat, Norazlina (2009)
The purpose of the current study was to examine the current crowd management practices among sport tourism event venue organizers in Kuala Lumpur and Selangor. Along with this exploratory and descriptive investigation of crowd management practices among sport tourism event venue organizers, relationships with safety performance were also being examined. A total of 23 sport tourism event venue managers in Kuala Lumpur and Selangor were approached to answer self administered questionnaires in this study. Relationships were determined using coefficient correlation, multiple regressions and chi-square. The findings revealed that sport tourism venue that hosted several sport tourism events annually practiced the crowd management strategies recommended in the literature. Evidently, many crowd management practices were carried out, as to ensure the general safety of spectators or visitors from accidents and incidents. In addition, the study found a strong relationship between crowd management and safety performance. Larger capacity event venue practices better crowd management than the smaller venues. Surprisingly, the study revealed that none of the sport venue managers had any qualification in Occupational Health and Safety even though it is highly related with the safety aspects for any organization.